Current issues in evaluating structural reforms within the Lisbon Process: Comments and recommendations about the Lisbon Methodology (LIME) Working Group - André Sapir (Bruegel, 2006)
André Sapir puts forward some comments and recommendations about the Lisbon Methodology (LIME) Working Group. This Policy Contribution was presented at the first meeting of LIME'S Working Group on 1 February 2007.
Keywords: 330; Lissabon Strategie